Clonagem, sequenciamento e modelagem molecular por homologia da sequência parcial de uma vicilina de genótipos de feijão-de-corda [Vigna unguiculata (L.) Walp.] contrastantes em relação à resistência ao caruncho Callosobruchus maculatus. - Silva, Bruno Henrique Maia (2014)
The cowpea bean [Vigna unguiculata (L.) Walp.] is a legume with high protein levels, largely cultivated and consumed in the Northeast of Brazil. Due to your economic importance, there are several studies that search resistant forms of cultivars of this kind of bean, as they is often attacked by different kinds of pests and predators. One of the most common is the weevil Callosobruchus maculatos. With the discovery of resistant cultivars for this insect many questions emerged about what biological component of the plant was responsible for such defensive action. Some studies suggest that this resistance is due to vicilin, which are reserve nutritious proteins, present in the seeds of cowpea. In this work, regions belonging to the vicilin gene of two contrasting cultivars in relation to resistence to weevil were sequenced, one resistant (IT81D-1053) and a susceptible (EPACE-10). These sequences, which come from several clones, were analyzed and thereby deducting its three-dimensional structure was made through a homology modeling using as template one 7S globulin from adzuki bean (Vigna angularis) identified as 2EA7 in the PDB database. Sequence analysis revealed that there are two regions highly variable in sequence from the vicilin gene, and these regions are rich in glutamine. Previous studies suggest that resistance to weevil occurs in the fact that the vicilin can bind to chitin and such glutamine rich regions are potentially chitin binding due to the high ability to form hydrogen bonds between the residues of glutamine and residues of N-acetylglucosamine. The structural analysis also supports this assumption, because the region rich in glutamine is very exposed, in relation to the protein surface, which facilitates the interaction of these amino acid residues with chitin. However more refined studies are needed to have a certainty of how is this interaction between vicilin and chitin, and if these same proteins are in fact fundamental in the resistance against the weevil.